1993
DOI: 10.1093/oxfordjournals.humrep.a137997
|View full text |Cite
|
Sign up to set email alerts
|

Fertilization and early embryology: Fertilization potential in vitro is correlated with head-specific mannose — ligand receptor expression, acrosome status and membrane cholesterol content*

Abstract: Normozoospermic men who do not fertilize human eggs in vitro constitute a clearly identifiable class of occult male factor infertility. We have studied the relationships between in-vitro fertilization (IVF) outcomes and the appearance of sperm surface mannose lectin/zona pellucida ligand activity measured by the binding of fluorescein isothiocyanate (FITC)-labelled mannosylated albumin. Of 338 semen specimens with normal profiles, 10 (2.96%) failed to fertilize in vitro (IVF-). Motile spermatozoa from six of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
0

Year Published

1995
1995
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(51 citation statements)
references
References 0 publications
2
49
0
Order By: Relevance
“…In support of Davis' model, some researchers reported that sperm cholesterol decreased when sperm were incubated in albumin-containing medium in vitro [10,14,[17][18][19], although in only one case [10] was the loss of cholesterol shown to be correlated with the sperm's becoming capacitated. Arguing against the loss of sperm cholesterol during incubation in vitro were reports that sperm cholesterol did not decrease or that the decrease was not statistically significant [20][21][22].…”
Section: Introductionmentioning
confidence: 91%
“…In support of Davis' model, some researchers reported that sperm cholesterol decreased when sperm were incubated in albumin-containing medium in vitro [10,14,[17][18][19], although in only one case [10] was the loss of cholesterol shown to be correlated with the sperm's becoming capacitated. Arguing against the loss of sperm cholesterol during incubation in vitro were reports that sperm cholesterol did not decrease or that the decrease was not statistically significant [20][21][22].…”
Section: Introductionmentioning
confidence: 91%
“…This is a widely accepted theoretical model that warrants continued investigation. Many studies have shown that albumin [7][8][9][10][11][12] and high-density lipoprotein (HDL) [13,14] present in the female genital tract facilitate the efflux of cholesterol that occurs during the early step of capacitation. HDL, probably derived from plasma, is the only class of lipoprotein present in bovine follicular and oviductal fluids [13,15,16].…”
Section: Introductionmentioning
confidence: 99%
“…This process helps to dispel the contents of the acrosome, including surface antigens and enzymes, for successful fertilization. D-mannose binding lectins on the sperm surface, for example, have been shown to help bind spermatozoa to the zona pellucida [39,40]. The acrosomal enzymes digest the outer acrosomal membrane and the plasma membrane to which it is attached.…”
Section: Capacitation and Acrosome Reactionmentioning
confidence: 99%